PEMBERDAYAAN MASYARAKAT PESISIR MELALUI PEMANFAATAN RUMPUT LAUT DI KELURAHAN PABIRINGA KECAMATAN BINAMU KABUPATEN JENEPONTO - Az-zahra, Diva Fhadillah; Mone, Ansyari; Sudarmi, Sudarmi (Universitas Muhammadiyah Makassar, 2023)
The purpose of this study was to find out how community empowerment was carried out by the Maritime Service. The research approach used was descriptive qualitative. By using data collection techniques through interviews Based on the results of research related to empowering coastal communities through the use of seaweed in Pabiringa Village, Binamu District, Jeneponto Regency, which was carried out by the Marine and Fisheries Service, Jeneponto Regency, it was quite good. This can be seen from several indicators of empowerment which include: enabling (creating) the local government creating an atmosphere that makes the potential of coastal communities in Pabiringa Village develop. Meanwhile, empowering strengthens the potential of coastal communities in Pabiringa Village through concrete steps by providing the necessary support and resources so that coastal communities can develop and improve their capabilities, skills and economic opportunities.